The length-biased power hazard rate distribution: Some properties and applications - Abdelfattah Mustafa; M.I. Khan (Statistics in Transition new series (SiTns), 2022)
In this article, the length-biased power hazard rate distribution has introduced and investi-gated several statistical properties. This distribution reports an extension of several prob-ability distributions, namely: exponential, Rayleigh, Weibull, and linear hazard rate. Theprocedure of maximum likelihood estimation is taken for parameters. Finally, the applica-bility of the model is explored by three real data sets. To examine, the performance of thetechnique, a simulation study is extracted.
Keywords: 519; length-biased; power hazard rate distribution; maximum likelihood estimation